WLE Program Brochure 2018/19: Connected thinking, compelling solutions - CGIAR Research Program on Water, Land and Ecosystems (2018)
Through connected thinking and compelling solutions, WLE’s research-for-development work considers not only the field, but also the landscape and system level impacts of agriculture: how decisions around soil, water, biodiversity and people interact and impact the big picture. This program brochure outline's WLE's approach, research themes and impacts.